Rencana Pelaksanaan Pembelajaran Dalam Kurikulum Merdeka - Dwi Luspita Sari; Maya Amarta; Rifin Rifin; Mustafiyanti Mustafiyanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Merdeka Curriculum is here as a breath of fresh air in the world of Indonesian education, bringing a spirit of independence for teachers and students to learn and teach with creativity. One of the important instruments in realizing the vision of Independent Learning is the Learning Implementation Plan (RPP) which has undergone a significant transformation compared to the 2013 Curriculum RPP (K13). The Independent Curriculum RPP is made more concise and focuses on essential points, so that it is easy for teachers to understand and use. Learning objectives are formulated clearly, measurably and oriented towards Learning Achievements (CP), ensuring learning is centered on the outcomes to be achieved. Teachers are encouraged to understand students’ learning profiles, including their interests, talents, learning styles and learning needs. This allows learning to be designed in a personalized and meaningful way for each individual.